The Digitalization of Learning Assessment - Awang, Mohd Isha (International Conference on Multidisciplinary Research, 2021)
Assessment is recognized as significant in the world of education. The field of assessment is seen as one of the most difficult areas to reform due to the various challenges faced by teachers and students during the process of learning. Changes to digital technology in teaching and learning activities have influenced the assessment process in all educational institutions. Current assessment method that is mainly summative is often described as outdated compared to the development of the current world of education which focuses on outcome-based education (OBE). In general, the development of digital technology has changed the implementation of teaching and learning activities which also involves learning assessment. New technologies and tools have long been seen as a new possibility for assessment due to their features or capabilities that are potentially beneficial as they offer a more holistic, immediate and engaging assessment experience. Nevertheless, past studies have concluded that the use of digital technology is not yet ‘transformative’ due to its limited innovation and because its use is still linked to traditional assessment methods. In general, this paper will address the digital technology in teaching practice and the assessment of learning. Keywords: Digitalization, Learning, Assessment, Formative, Summative